Digital Competence of Young Adults in Poland - Ćwiek, Małgorzata; Maj-Serwatka, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
Digital transformation is a challenge for many areas of modern society functioning. The effects of digitalisation are particularly noticeable in the labour market and are expressed, among others, in new requirements of employers both for professionally active people and those entering the labour market. Technological advances and automation are reducing the number of low skilled jobs. Moreover, employees are required to be more flexible. As a consequence, there is a need to adapt to changing trends in the labour market, and to constantly learn and acquire new competences, including digital competences. This paper aims to identify vulnerabilities regarding digital competences and their determinants amongst young adults in Poland. Furthermore, detailed objectives were defined: (1) assessment of the level of digital competences of young adults in Poland; (2) identification of the gaps in this area; (3) identification of factors differentiating the level of digital competences. The catalogue of competences under study was taken from the European Digital Competence Framework, which includes 21 digital competences grouped into five areas: (information and data literacy; communication and collaboration; digital content creation; safety; problem solving). To achieve the objective, a nationwide survey was conducted. The sample consisted of 1,000 young adult respondents (aged 18–30), with at least secondary education, selected by quotas from panel participants. The research methods used statistical analysis, including descriptive statistics, regression modelling (stepwise regression), as well as t-tests for independent samples, and One-Way ANOVA. Research results indicate that digital competences of young adults vary depending on the area. The respondents are aware of their insufficient skills, especially in the area of digital content creation (skills connected with programming). A relatively considerable share of individuals have no intention of acquiring these competences as part of lifelong learning. Self assessment of competences also indicates that their level differs due to individuals’ gender, age, level of education, and profile of education.